The Ever-Expanding Pseudomonas Genus: Description of 43 New Species and Partition of the Pseudomonas putida Group - Girard, Léa; Lood, Cédric; Höfte, Monica; Vandamme, Peter; Rokni-Zadeh, Hassan; van Noort, Vera; Lavigne, Rob; De Mot, René (Microorganisms (Basel), 2021)
The genus Pseudomonas hosts an extensive genetic diversity and is one of the largest genera among Gram-negative bacteria. Type strains of Pseudomonas are well known to represent only a small fraction of this diversity and the number of available Pseudomonas genome sequences is increasing rapidly. Consequently, new Pseudomonas species are regularly reported and the number of species within the genus is constantly evolving. In this study, whole genome sequencing enabled us to define 43 new Pseudomonas species and provide an update of the Pseudomonas evolutionary and taxonomic relationships. Phylogenies based on the rpoD gene and whole genome sequences, including, respectively, 316 and 313 type strains of Pseudomonas, revealed sixteen groups of Pseudomonas and, together with the distribution of cyclic lipopeptide biosynthesis gene clusters, enabled the partitioning of the P. putida group into fifteen subgroups. Pairwise average nucleotide identities were calculated between type strains and a selection of 60 genomes of non-type strains of Pseudomonas. Forty-one strains were incorrectly assigned at the species level and among these, 19 strains were shown to represent an additional 13 new Pseudomonas species that remain to be formally classified. This work pinpoints the importance of correct taxonomic assignment and phylogenetic classification in order to perform integrative studies linking genetic diversity, lifestyle, and metabolic potential of Pseudomonas spp.